Methods for estimating the burden of antimicrobial resistance: a systematic literature review protocol - Naylor,NR; Silva,S; Kulasabanathan,K; Zhu,N; Knight,G; Robotham,J (Systematic Reviews, 2016)
Background:Estimates of the burden of antimicrobial resistance (AMR) are needed to ascertain AMR impact, evaluate interventions and to allocate resources efficiently. Recent studies have estimated health, cost and economic burden relating to AMR, with outcomes of interest ranging from drug-bug resistance impact on mortality in a hospital setting to total economic impact of AMR on the global economy. However, recent collation of this information has been largely informal, with no formal quality assessment of the current evidence base (e.g. with predefined checklists). This review therefore aims to establish what perspectives and resulting methodologies have been used in establishing the burden of AMR, whilst also ascertaining the quality of these studies. Methods:The literature review will identify relevant literature using a systematic review methodology. MEDLINE, EMBASE, Scopus and EconLit will be searched utilising a predefined search string. Grey literature will be identified by searching within a predefined list of organisational websites. Independent screening of retrievals resultswill be performed in a two-stage process (abstracts and full texts), utilising a pre-defined inclusion and exclusion criteria. Data will be extracted into a data extraction table and descriptive examination will be performed. Study quality will be assessed using the Newcastle-Ottawa scales and the Philips checklists where appropriate. A narrative synthesis of the results will be presented. Discussion:This review will provide an overview of previous health, cost and economic definitions of burden and the resultant impact of these different definitions on the burden of AMR estimated. The review will also explore the methods that have been used to calculate this burden and discuss resulting study quality. This review can therefore act as a guide to methods for future research in this area.Trial Registration:This review has been registered with the PROSPERO International Prospective Regis